PROBLEMS AND SOLUTIONS OF PROTECTING MOTHERHOOD AND CHILDHOOD IN UZBEKISTAN IN THE 1920S-1960S (In the Case of the Southern Regions) (Modern American Journal of Social Sciences and Humanities, 2025)
Research on the protection of motherhood and childhood shows that the socio-economic living conditions of the population, including material security, housing, working conditions, recreation, education, culture, traditions, nutrition, and other factors, directly and indirectly affect the health of future generations.